Nano-biochar: recent progress, challenges, and opportunities for sustainable environmental remediation - Bhandari, Geeta; Gangola, Saurabh; Dhasmana, Archna; Rajput, Vishal; Gupta, Sanjay; Malik, Sumira; Slama, Petr (Frontiers in Microbiology, 2023)
Biochar is a carbonaceous by-product of lignocellulosic biomass developed by various thermochemical processes. Biochar can be transformed into "nano-biochar" by size reduction to nano-meters level. Nano-biochar presents remarkable physico-chemical behavior in comparison to macro-biochar including; higher stability, unique nanostructure, higher catalytic ability, larger specific surface area, higher porosity, improved surface functionality, and surface active sites.Nano-biochar efficiently regulates the transport and absorption of vital micro-and macronutrients, in addition to toxic contaminants (heavy metals, pesticides, antibiotics). However an extensive understanding of the recent nano-biochar studies is essential for large scale implementations, including development, physico-chemical properties and targeted use. Nanobiochar toxicity on different organisms and its in-direct effect on humans is an important issue of concern and needs to be extensively evaluated for large scale applications . This review provides a detailed insight on nanobiochar research for (1) development methodologies, (2) compositions and properties, (3) characterization methods, (4) potentiality as emerging sorbent, photocatalyst, enzyme carrier for environmental application, and (5) environmental concerns.